ANTHROPOLOGICAL PROBLEMS IN THE PHILOSOPHICAL WORKS OF RUSSIAN SPIRITUAL ACADEMIES' TEACHERS OF THE EARLY 20TH CENTURY - M. A. Ershova (Russian State Vocational Pedagogical University, 2015)
The paper deals with the analysis of philosophical and theological creativity of Russian theological academies' teachers of the early 20th century. The aim of this study is to identify the impact of methodological foundations' changes of philosophical-theological quest on the teachers of Russian theological academies and the educational process itself in theological schools. Methods. The author focuses on the content of training courses delivered in the theological academies in the first two decades of the 20th century; problem statement peculiarities; aspect and priority choice in the fundamental researches conducted by the teachers of these schools. The applied methods include the comparative method, analysis, synthesis, method of abstraction, other philosophical and scientific methods. Results. The author comes to the conclusion that the changes of methodological installations in scientific research representatives of spiritual and academic theism beginning of the 20th century can be compared with similar studies of the nineteenth century. It is mentioned that reorientation of a number of prominent representatives of spiritual and academic theism from scholastic methods, speculative psychology and metaphysics towards Patristics, asceticism and personal experiences allows us to propose this movement as West-European Philosophy searches of the same period. Thus, V. I. Nesmelov sees the basis of any religious teachings in the experience of human cognition. M. M. Tareev draws up his own moral theology reading course based on the personal experience living the Gospel Book. Archimandrite Sergious (Stragorodsky) interprets the topic of finding salvation not against the background of the changes in God, but from the standpoint of the changes that occur in humanity. Bishop Theodore (Pozdeevsky), Archbishop Hilarion (Troitsky) and Bishop Barnabas (Belyaev) make known scholasticism as epistemological malice characterizing the specifics of theological knowledge necessary to base their intellectual efforts on the personal experience of the struggle against the passions; therefore, they see the new basis of theology in asceticism. Professor S. V. Troitsky considers marriage as the key problem for religion and philosophy of the early 20th century. Professor S. S. Glagolev sees the descent of a man as the crossing point of religion and science. The author mentions that despite some heterogeneity of the proposed concepts, there is an obvious General anthropological orientation that had an impact on the educational process changes in theological academies (seminaries). Scientific novelty. The author systemizes and sums up anthropologic views of the most recognizable ecclesiastical academics in the early 20th century. Representation and analysis of anthropologic problematics in philosophical and religious papers of the Russian ecclesiastical education stage of development signify essential agreement among Russian and Western sophists; they had been discussing the same problem - a human being. The author points out that their discussions were not absolutely the same, but it gives the reason to regard the anthropology of the early 20th century as modern Philosophy; and this difference allows academic anthropology to avoid classic and non-classic types of philosophy. Practical significance. The research outcomes can be used for further understanding development of the all European searching process of the early 20th century. Received by the author of the study findings provide its scientific innovation. The results of this study can be used in assessing the role of theological academies in European cultural processes and culture of the Russian society of the early 20th century; research findings can enrich the content of the lectures on the History of Philosophy, Russian History, European History, Cultural Studies and other Humanities (non-science disciplines).